PENDIDIKAN KRISTEN DAN SPIRITUALITAS DI ERA DIGITAL: TANTANGAN, PELUANG, DAN STRATEGI - Parulian Hutasoit; Dandi Saputra; Iren Sihombing (Voice of HAMI: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
AbstractThe current digital era is experiencing increasingly modern technological developments, making it easier for humans to obtain various information, be it information that is spiritually constructive or information that is destructive to every Christian value and our spirituality. At this time, opportunities have opened up for every believer to explore life in accordance with the values of Spirituality. Christian education and spirituality must undergo a transformation in order to adapt to the current developments. With this transformation, it is hoped that Christian education and Christian spirituality will be able to maintain their existence by adhering to the truth of God's Word. In addition, there are challenges for Christian education and spiritual values that must be faced at this time. This article contains how Christian education and spirituality develop in the digital era and the use of technology wisely and continue to maintain Christian values and spiritual values. This study uses a library research method to analyze the development of Christian and spiritual education in the digital era. Therefore, researchers provide findings on how to apply technology to Christian education and spirituality so that technological advances not only have negative impacts, but also have very good opportunities to be used and applied. Keywords: Chirstian Education;  Spirituality;  Digital Era AbstrakEra digital saat ini mengalami perkembangan teknologi yang semakin modern, sehingga memudahkan manusia untuk mendapatkan berbagai informasi, baik itu informasi yang bersifat membangun spritualitas atau informasi yang bersifat meruntuhkan setiap nilai Kristen dan spiritualitas kita. Pada saat ini telah terbuka peluang bagi setiap orang percaya untuk mendalami kehidupan sesuai dengan nilai Spiritualitas. Pendidikan Kristen dan spiritualitas harus mengalami transfomasi guna menyesuaikan perkembangan zaman yang ada. Dengan adanya transformasi tersebut, diharapkan pendidikan Kristen dan spritualitas Kristen mampu mempertahankan eksistensinya dengan tetap berpegang pada kebenaran Firman Tuhan. Selain itu ada tantangan tersendiri bagi pendidikan Kristen dan nilai spiritualitas yang harus dihadapi pada saat ini. Artikel ini berisi bagaimana pendidikan Kristen dan spiritualitas berkembang di era digital dan pemanfaatan teknologi dengan bijak dan terus mempertahankan nilai kekristenan dan nilai spiritualitas. Penelitan ini menggunakan metode penelitian kepustakaan untuk menganalisis perkembangan pendidikan Kristen dan spiritual di era digital. Oleh karena itu, peneliti memberikan temuan mengenai bagaimana melakukan penerapan teknologi pada pendidikan Kristen dan spiritualitas sehingga kemajuan teknologi bukan hanya memberikan dampak negatif, tetapi juga memiliki peluang yang sangat baik untuk digunakan dan diterapkan. Kata kunci: Pendidikan Kristen; Spiritualitas; Era Digital